ChemInform Abstract: Asymmetric Aldol Reactions Between Acetone and Benzaldehydes Catalyzed by Chiral Zn2+ Complexes of Aminoacyl 1, 4, 7, 10‐Tetraazacyclododecane: Fine‐Tuning of the Amino‐Acid Side Chains and a Revised Reaction Mechanism. Issue 8 (25th February 2014) - Itoh, Susumu; Tokunaga, Takuya; Sonoike, Shotaro; Kitamura, Masanori; Yamano, Akihito; Aoki, Shin
Abstract The yields and enantioselectivities of the reaction are improved compared to the known methods.